A qualidade das informações na percepção de integrantes da cadeia de suprimentos interna: o caso do serviço Netsuper da CTBC Telecom - Silva, Valéria Vieira da (2007)
To grow in competitive environments, the organizations have to improve processes and people abilities thru information technology and make strategic decisions about information quality demand, in their in-house supply chains, to delivery quality service. However, guarantee customers demand and satisfy employees needs, request appropriate information management, what can be expensive and difficult. For that reason, information supply thru the process chain, demands an efficient structure to understand what these subsidies symbolize and why they are so important to delivery services with quality. Thus, the objective of this research is to evaluate the information flow quality in a services organization in-house supply chain, to identify the information quality dimensions that allow the progress of planned results attainment. For this, it was conduced a case study at CTBC Telecom, a regional telecommunications player in Brazilian southeastern, with a good social-economics representation. The specific focus of appreciation was the NetSuper, a broad band service (ADSL). The analysis identified the main information quality dimensions to the executives and their distortions that compromise these subsidies quality. For this, CTBC Telecom inhouse supply chain was drawn, the information flow of this chain was justified, the dimensions quality were ranked to prioritize those most important at the managers perception and the complete view of information flow process was described. Afterwards, the salesmen information knowledge level, about NetSuper service, was identified and also their satisfaction with the quality of information, processes and other subsidies for sales, for then, verifies the information quality loss. The research is descriptive and, predominantly qualitative. For data gathering it had been applied half-structuralized interviews with managers, document analyses and a structuralized questionnaire to a representative salesmen sample of direct and indirect channels. Data were tabulated and interpreted applying frequency analysis, dynamic tables and graphical exits. This case study evidenced that managers perceive the information quality loss, confirmed by the questionnaires data from salespeople, which evidence their lack of knowledge about the product advantages and attributes. Sales force sample highlighted some specific needs on quality dimensions that would improve the information quality flow. But, by the results, it was evidenced that the most important quality dimensions for CTBC Telecom Company are not dealt with priority in the Organization, what demonstrate that a model of integrated management of processes is needed. Further on this, it was recommended a scheme for an information quality management structure, referenced on the theoretical models of Supply Chain Management (Lambert, 2004) and Services Quality Gaps (Zeithaml and Parasuraman, 2004). Subsequent studies should include suppliers and consumers in the analysis, enclosing, by this, all relationships of the chain in which the information flows. Another investigative aspect is the adoption of measurement patterns of the information quality for all actors of the in-house supply chain, to survey the quality of the information.